PERANAN PUPUK ORGANIK DALAM PENINGKATAN PRODUKTIVITAS TANAH DAN TANAMAN - Hartatik, Wiwik; Husnain, Husnain; Widowati, Ladiyani R. (Jurnal Sumberdaya Lahan, 2015)
Abstrak: Pupuk organik berperan dalam meningkatkan kesuburan fisik, kimia dan biologi tanah serta mengefisienkanpenggunaan pupuk anorganik. Kualitas dan komposisi pupuk organik bervariasi tergantung dari bahan dasar kompos dan prosespembuatannya. Penggunaan tanaman legum baik berupa tanaman lorong (alley cropping) maupun tanaman penutup tanah (covercrop) serta bahan organik insitu, perlu diintensifkan untuk mendukung pemanfaatan pupuk organik non komersial danpemulihan kesuburan tanah.Pemberdayaan masyarakat dan kelompok tani dalam pengadaan pupuk organik dapat dilakukanmelalui: a) melatih petani membuat pupuk organik insitu yang berasal dari kotoran ternak dan sisa tanaman yangdikomposkan;b) mendorong petani melakukan diversifikasi usaha pertanian berbasis ternak; dan c) mendorong petanimelakukan pengelolaan bahan organik insitu terutama pada lahan kering. Pemanfaatan pupuk organik telah diterapkan dalamsistem budidaya pertanian organik (organic farming) dan System rice of intensification (SRI). Pemberian pupuk organik yangdikombinasikan dengan pupuk anorganik, telah diterapkan dalam sistem pengelolaan tanaman terpadu (PTT), sistem integrasipadi/palawija dan ternak (SIPT), sistem pertanian mandiri yang mengintegrasikan ternak dan tanaman crop livestock system(CLS).Abstract: It is inevitable that organic fertilizer plays a major role in increasing the fertility of the physical, chemical and biologicalas well as the efficient use of inorganic fertilizers. The main composition of organic fertilizer when it decomposes will consist ofmostly water and cellulose, hemiselulose, lignin, and a small portion main macro nutrients, secondary macro nutrients, microelements and silica. There is also a growth regulating enzymes and vitamins as a byproduct of microbial decomposition. The maincomponent or specific parameters have a major role and the speed of the process of transformation of organic fertilizer into theform of mineral nutrients and the end product is humus. The significance of organic fertilizer is widely recognized by agriculturalresearchers and practitioners. In addition the use of organic fertilizers in paddy fields and dry land cultivation system ofagriculture that combines inorganic fertilizer and organic, has strived implemented by the government in this case the Ministry ofAgriculture that the system of integrated crop management (ICM), system integration paddy/crops and livestock (SIPT), anindependent agricultural systems that integrate livestock and crop plants livestock system (CLS). If the awareness of farmers onthe use of organic fertilizers increases, the availability of both in situ and have to come from outside should be available insufficient quantity and good quality. Technological innovation of Agricultural Research and Development Agency to support theuse of organic fertilizers continue to research and develop. Currently available guidebooks and technological innovation, such asland management guidelines, management guidelines of organic materials and organic fertilizer, granular organic fertilizerproduct (Tithoganik, POG, POCr), and decomposers products to accelerate the process of decomposition (such as M-dec).Opportunities and challenges in increasing stakeholder awareness is not a barrier in optimizing organic fertilizer. The key is thesynergistic integration between institutions regulatory, technical institutions, Research Agency, producers and users in theimplementation of socialization, production, guidance and supervision.